Intramedullary Nailing of Paediatric Tibial Fractures: Comparison between Flexible and Rigid Nails. (June 2021) - Widbom-Kolhanen, S.; Helenius, I.
Purpose: To describe patient characteristics and to compare outcomes of children undergoing rigid intramedullary nailing of tibial fractures as compared with those operated on using elastic intramedullary nailing. Methods: A retrospective review of 26 children who have undergone flexible intramedullary nailing of tibial fractures and 30 children with rigid nailing at our university hospital between 2008 and 2017. The patient charts and radiographs were evaluated to identify demographic characteristics and several variables were measured preoperatively, as well as 6–12 weeks postoperatively in addition to final follow-up radiographs. Results: Twenty-six patients (26/26, 100%) treated with a flexible nail and 14 patients (14/30, 46.7%) treated with a rigid nail had open proximal tibial physis (p < 0.001). An acceptable postoperative alignment was obtained in 20 patients (20/26, 76.9%) in the elastic stable intramedullary nail group and in 29 patients (29/30, 96.7%) in the rigid group (p = 0.026). Some complications occurred in four patients (4/26, 15%) in the elastic stable intramedullary nail population and seven patients (7/30, 23%) in the rigid intramedullary nail population (p = 0.46). Malunion occurred in six patients (6/26, 23%) in the elastic stable intramedullary nail group and in none of the patients treated with a rigid intramedullary nail (p = 0.005). Conclusion: Younger children with tibial fractures who weight 50 kg or less and with proximal tibial growth plates wide open can be treated with elastic stable intramedullary nail while more mature adolescents benefit from rigid intramedullary nailing.